Dietary nitrate supplementation reduces the O2 cost of walking and running: a placebo-controlled study - Lansley, K. E.; Winyard, P. G.; Fulford, J.; Vanhatalo, A.; Bailey, S. J.; Blackwell, J. R.; DiMenna, F. J.; Gilchrist, M.; Benjamin, N.; Jones, A. M. (Journal of Applied Physiology, 2011)
Dietary supplementation with beetroot juice (BR) has been shown to reduce resting blood pressure and the O2 cost of submaximal exercise and to increase tolerance to high-intensity cycling. We tested the hypothesis that the physiological effects of BR were consequent to its high NO3- content per se, and not the presence of other potentially bioactive compounds. We investigated changes in blood pressure, mitochondrial oxidative capacity (Qmax), and physiological responses to walking and moderate- and severe-intensity running following dietary supplementation with BR and NO3--depleted BR [placebo (PL)]. After control (nonsupplemented) tests, nine healthy, physically active male subjects were assigned in a randomized, double-blind, crossover design to receive BR (0.5 l/day, containing ~6.2 mmol of NO3-) and PL (0.5 l/day, containing ~0.003 mmol of NO3-) for 6 days. Subjects completed treadmill exercise tests on days 4 and 5 and knee-extension exercise tests for estimation of Qmax (using 31P-magnetic resonance spectroscopy) on day 6 of the supplementation periods. Relative to PL, BR elevated plasma NO2- concentration (183 ± 119 vs. 373 ± 211 nM, P < 0.05) and reduced systolic blood pressure (129 ± 9 vs. 124 ± 10 mmHg, P < 0.01). Qmax was not different between PL and BR (0.93 ± 0.05 and 1.05 ± 0.22 mM/s, respectively). The O2 cost of walking (0.87 ± 0.12 and 0.70 ± 0.10 l/min in PL and BR, respectively, P < 0.01), moderate-intensity running (2.26 ± 0.27 and 2.10 ± 0.28 l/min in PL and BR, respectively, P < 0.01), and severe-intensity running (end-exercise O2 uptake = 3.77 ± 0.57 and 3.50 ± 0.62 l/min in PL and BL, respectively, P < 0.01) was reduced by BR, and time to exhaustion during severe-intensity running was increased by 15% (7.6 ± 1.5 and 8.7 ± 1.8 min in PL and BR, respectively, P < 0.01). In contrast, relative to control, PL supplementation did not alter plasma NO2- concentration, blood pressure, or the physiological responses to exercise. These results indicate that the positive effects of 6 days of BR supplementation on the physiological responses to exercise can be ascribed to the high NO3- content per se.